Предмет: Алгебра,
автор: Аноним
Упростите выражение:
Ответы
Автор ответа:
0
cos x/(1+sin x) + tg x = cos x/(1+sin x) + (sin x / cos x).
Приводим к общему знаменателю:
(cos²x + sin²x + sin x) / (cos x*(1+sin x).
Учитывая, что cos²x + sin²x = 1, получаем:
(1 + sin x) / (cos x*(1+sin x).
После сокращения : 1 / cos x = sec x.
Приводим к общему знаменателю:
(cos²x + sin²x + sin x) / (cos x*(1+sin x).
Учитывая, что cos²x + sin²x = 1, получаем:
(1 + sin x) / (cos x*(1+sin x).
После сокращения : 1 / cos x = sec x.
Похожие вопросы
Предмет: Геометрия,
автор: Revaz33
Предмет: Математика,
автор: Аноним
Предмет: Русский язык,
автор: marklevsk7878
Предмет: Математика,
автор: Аноним
Предмет: Химия,
автор: lapo4ka20131